The Associated Meniscal Tears and Associated Risk Factors in Concomitant ACL Injuries of the Knee: A Retrospective Analysis - Kalawar, Rosan Prasad Shah; Chaudhary, Pashupati; Rijal, Raju; Pokharel, Bishnu (Birat Journal of Health Sciences, 2020)
Introduction: The pattern of meniscus tear has significant impact onsubsequent rehabilitation and functional outcome as theyare usually associated with ACL injury.Knowledge about associated meniscus tear helps to identifypatients in the early post-traumatic phase. Objectives: To study meniscus tear patterns and associationbetween different tear patterns of meniscus in ACLinjured subjects and to identify potential demographic andother associated risk factors. Methodology: Routine arthroscopic findings database of 54 patientsoperated for primary ACL reconstruction from January 2017to December 2018 was used to study associated tear of meniscus. Based on arthroscopic evaluation, cases weregrouped into meniscus having no tear, minor tear and majortear. Major tear included complete radial tears, root tearsand unstable longitudinal tears including bucket-handletears. Result: Totalarthroscopycasesinthestudydurationwere124.Ofthose,43% (n=54) underwent ACL reconstruction (ACLR) for tornACL. Among the patients who underwent ACLR, 58% had notear, 26%hadminortears, and16%hadmajortears ofthemeniscus. Therewere significant differencesbetweenthree groups for gender, age groupsandmechanism of injury. Risk factors formajortearsweremalegenderandage<30years.Minorandmajortears were associated with a contact injury. Conclusion: Male, age <30 years and history of contact injury havehigh risks for having an associated meniscus tear. Earlyreferral to magnetic resonance imaging and/or arthroscopyis recommended to allow meniscus repair in a timelymanner.